Changes in early soybean mycorrhization with the application of seaweed extracts to seeds - Dias, Marcos Altomani Neves (2019)
Sustainable agriculture practices include a better exploitation of soil natural resources. Arbuscular mycorrhizal fungi (AMF) plays an important role in this context, with native communities in soils that establishes a mutualistic association with most plant species and maximizes their access to mineral nutrients, especially phosphorus. Seed treatment may consist in a good alternative to stimulate AMF root colonization, since early stages of crop growth, by using biostimulant formulations applied to seeds. This research had the objective to evaluate the early mycorrhization of soybean plants in response to seaweed extracts applied to seeds. The treatments consisted of a control (CTR, distilled water), two seaweed extracts, from Ascophyllum nodosum (ANE) and Ecklonia maxima (EME) species and a synthetic formulation containing formononetin (FOR), commercially used as mycorrhization stimulant. The first experiment was conducted in greenhouse, with the aim to evaluate different parameters of soybean early growth and development and AMF root colonization in response to the seed treatments, under different rates of phosphorus added to the soil (0, 50, 100 and 200 mg.dm-3). The second experiment was conducted in growth chamber, with the objective to evaluate qualitative and quantitative aspects of mycorrhization in response to the seed treatments with biostimulants, at early plant growth stages. In this experiment, the influence of treatments on the structure of AMF, bacterial and fungal communities in the soybean rhizosphere were analyzed, through PCR/T- RFLP fingerprinting. Phosphorus rates applied to soil significantly influenced (P<0.10) biometric and physiological parameters of soybean plants, while the seed treatments only influenced leaf chlorophyll content and nitrogen balance at a significant level, despite some trends to increase leaf area, shoot dry mass and nodulation. Formononetin applied to soybean seeds increases AMF root colonization compared to control, independently of P rate applied to soil, while ANE and EME presented intermediate values for this parameter, not differing from both control and formononetin. When considered some qualitative parameters of mycorrhiza establishment, such as frequency and intensity of mycorrhization, both synthetic and natural biostimulants presented significant improvements, with EME and FOR providing higher values in general. The phenological stage of soybean significantly influenced AMF, bacterial and fungal community structures in rizosphere, while the biostimulant seed treatments only significantly influenced the bacterial community. However, a relatively large variation in the microbial community structures could be attributed to the interaction between phenological stage of plants and the seed treatment with biostimulants.